Design of a Cyber-Physical Human Smart Workstation that balance the human wellbeing and the productivity (2021)
Cyber-physical productions systems (CPPS) play a fundamental role in the fourth industrial revolution along with human-centered design. The consideration of these two establishes the concept of human-centered Cyber-physical production systems (H-CPPS), which is defined as a system that mainly support humans, machines, and software to integrate virtual and physical worlds. Certainly, H-CPPS are not intended to substitute the human operators in the industry but rather to support and augment their capabilities, as well as ensure their well-being. Nowadays, there is limited information for workstation design from an ergonomic perspective and the method for including this workstation on a CPPS. In this paper, it is proposed a methodology that allows to identify the industrial requirements and ergonomic considerations to be considered in a human-centered workstation design. Firstly, this approach aims to evaluate a set of general tasks from the manufacturing industry, assess the ergonomic risk inherent to their execution and identify the technological enablers to balance the human productivity and wellbeing. Secondly, this approach provides a set of guidelines for deploying a generic human-centered workstation with ergonomic considerations. Lastly, this paper constructed a human-centered workstation within a case study, as a proof-of-concept of the proposed methodology. Statistical tests were applied to find significant differences and correlations of the variables between the scenarios. The results from the experiments demonstrated that a human-centered workstation with real time cognitive and physical support contribute to decrease the ergonomic risk for industrial operators, and impact positively the operator’s productivity.